PENINGKATAN KETERAMPILAN PETERNAK MELALUI PELATIHAN BUDIDAYA HIJAUAN MAKANAN TERNAK UNGGUL DI KELURAHAN WATUMOTOBE, KECAMATAN KAPONTORI, KABUPATEN BUTON - Badaruddin, Rusli; Saili, Takdir; Ido, Irfan; Ibrahim, Irianto; Syamsuddin, Syamsuddin; Munadi, La Ode Muh. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Watumotobe Village in Kapontori District, Buton Regency, has the potential to develop forage (HMT) to support the availability of quality feed for local livestock. However, the limited knowledge of local farmers regarding superior HMT cultivation techniques is a challenge. This community service program aims to improve the skills of farmers through training in planting HMT such as odot grass, molato, red elephant grass, pakchong, and indigofera. The training method involves delivering interactive materials, field practice in demonstration plots, and technical assistance in plant maintenance. The results of the activities showed an increase in understanding and skills of farmers in cultivating HMT, which is expected to support independent and sustainable livestock feed security. This program also encourages cooperation between farmers in managing local forage resources as a step towards feed self-sufficiency in Buton Regency.